Opportunities of Geometric Documentation of Historic Buildings with Terrestrial Laser Scanner, Examples from Aksaray/Turkey - Armağan Güleç Korumaz; Grazia Tucci; Mustafa Korumaz; Valentina Bonora (Iconarp International Journal of Architecture and Planning, 2018)
Detailed and accurate measurements can be done by using laser scanning technology compared to conventional methods in documentation of cultural heritage. Accuracy of measured data directly affects the protection of historical buildings and decision-making process. By processing laser scanning data, multipurpose 3d models can be obtained and all work and results can be shared via internet. Moreover, a detailed analysis of the building can be made with this data and it can be transferred to all related engineering and archeological fields. Despite the advantages of this technology, it has not been used widely yet in production of architectural projects. High cost of equipment and data processing software have been seen as main obstacles for widespread using of this technology. As well as, lack of integration of this topic into architectural education and less number of researcher studying in this field restrict the use of laser scanner.  In this paper, evaluations were made in order to define the possibilities by using laser scanner technologies in process of restoration projects of which number is getting increased in last decades in Turkey. Positive and negative aspects of technology observed in survey process were given with a case study, a small traditional house in province of Aksaray and some reviews related to potential use of laser scanner technologies were made in Turkey.